Faithful hiring: An exploration of pastoral hiring within the Canadian Evangelical Church - Bonis, Christopher R. (HTS teologiese studies, 2023)
The pastoral role is a significant leadership function within the global evangelical church and is critical to the ongoing health, nurturing and spiritual development of the church and its members. There is limited literature and reflection on hiring for the church, yet the selection of a pastoral leader is more than an employment exercise as it involves important Christian values, perceptions and priorities of the church and the denomination. This article records a study on pastoral hiring process within a significant evangelical denomination in Canada. It uses a descriptive, multiple case-study approach involving four churches engaged in a pastoral search process. Findings revealed a convergence between church practices and typical organisational processes with pragmatic strategies for hiring decisions. In a secularising society of Canada, it is especially important that the church critically reflects on maintaining scriptural values on its hiring practices and not be shaped by the commercially driven business context to distinguish ethical practice and maintain its Christian witness.Contribution: This study provides new knowledge in the field of congregational studies on a much-neglected area of Christian practice, motivating for critical reflection and scriptural integrity within pastoral hiring processes.